The criminalisation of social policy in neoliberal societies - Kiely, Elizabeth; Swirak, Katharina (Bristol University Press, 2021)
From anti-immigration agendas that criminalise vulnerable populations, to the punishment of the poor and the governance of parenting, this timely book explores how diverse fields of social policy intersect more deeply than ever with crime control and, in so doing, deploy troubling strategies. The international context of this book is complemented by the inclusion of specific policy examples across the themes of work and welfare; borders and migration; family policy; homelessness and the reintegration of justice-involved persons. This book incites the reader to consider how we can reclaim the best of the 'social' in social policy for the twenty-first century.